Loss averse depositors and monetary policy around zero - Christian Stettler (ETH Zurich, KOF Swiss Economic Institute, 2020)
Recent experience from Europe and Japan shows that commercial banks generally pass negative short-term policy rates on to wholesale depositors, such as insurances and pension funds. Yet, they refrain from charging negative rates to ordinary retail customers. This paper asks whether the existing evidence on the inverse relationship between market experience and the degree of loss aversion can explain this transmission pattern. To this end, I allow for loss averse depositors within a simple two-period differentiated products duopoly with switching costs. It turns out that if depositors are especially averse to negative deposit rates, banks keep deposit rates at zero as policy rates decline, while accepting squeezed and possibly negative deposit margins. The lowest current policy rate at which the banking system is willing to shield depositors from a negative deposit rate decreases with increasing i) degrees of loss aversion; ii) levels of switching costs; and iii) market expectations about the future policy rate. A calibration of the model indicates how low central banks could effectively go without taking steps to make paper currency more costly.
hdl:20.500.11850/409517
Keywords: D43; E43; E52; E58; G21; L13; 330; Deposits; effective lower bound; loss aversion; negative interest rates